2015
DOI: 10.5935/1806-0013.20150061
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia: peripheral and central mechanisms

Abstract: BACKGROUND AND OBJECTIVES: Trigeminal neuralgia is one of the most common neuropathic pains that compromise head and neck. It manifests as shock or burning pain normally evoked by non-noxious facial stimulations. Its etiopathology is not totally understood, but it is known that different mechanisms contribute to the establishment and maintenance of pain. This study aimed to address current contexts of epidemiology, diagnosis, management and pathophysiological mechanisms underlying trigeminal neuralgia in perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…After nerve injury, an inflammatory process leads to the release of many pro-inflammatory mediators, which participate in peripheral sensitization, promoting an excessive release of neurotransmitters [ 94 ]. Together with the inflammatory process, neuropeptides and degenerative changes affecting the nervous fibers are also crucial peripheral mechanisms [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…After nerve injury, an inflammatory process leads to the release of many pro-inflammatory mediators, which participate in peripheral sensitization, promoting an excessive release of neurotransmitters [ 94 ]. Together with the inflammatory process, neuropeptides and degenerative changes affecting the nervous fibers are also crucial peripheral mechanisms [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this ascending pathway, noxious information is modulated by both local and descending pain modulatory pathways that either inhibit or facilitate the transmitted sensory information [9,10]. Descending inputs to the Vc arise from the primary somatosensory cortex (SI), secondary somatosensory cortex (SII), insula and from the Rostral Ventromedial Medulla (RVM) [8,11,12,13]. Eventually, the interpretation of noxious stimuli is influenced by a number of affective and cognitive factors that modulate pain.…”
Section: Trigeminal Pain Pathwaysmentioning
confidence: 99%
“…Possible causes include nerve trauma [1], compression of the trigeminal nerve root as in trigeminal neuralgia [2], demyelinating disorders, such as multiple sclerosis [3], neoplastic infiltration [4], and familial disorders, such as Charcot-Marie-Tooth disease [5], and secondary to herpetic infections [6]. In many cases, the cause of the neuropathic changes are not understood, however it has been suggested that dysfunction of both peripheral or central nervous systems may contribute [2,7,8]. Orofacial pain conditions are difficult to treat in clinical practice and are often confused with dental pain.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Previous studies of task fMRI in CTN have examined whether this syndrome stems from the central mechanism of a “pain matrix”. 3 , 4 However, variabilities in the activation results obtained by these task-related fMRI studies are quite large. One important reason may be that patients with CTN continuously process dull pain, therefore trigeminal neuralgia is easily concealed by these background activities, leading to greater variations in the functional activation.…”
Section: Introductionmentioning
confidence: 99%